Geographies of privilege - Twine, France Winddance; Gardener, Bradley (Routledge, 2013)
How are social inequalities experienced, reproduced and challenged in local, global and transnational spaces? What role does the control of space play in distribution of crucial resources and forms of capital (housing, education, pleasure, leisure, social relationships)? The case studies in Geographies of Privilege demonstrate how power operates and is activated within local, national, and global networks. Twine and Gardener have put together a collection that analyzes how the centrality of spaces (domestic, institutional, leisure, educational) are central to the production, maintenance and transformation of inequalities. The collected readings show how power--in the form of economic, social, symbolic, and cultural capital--is employed and experienced. The volume's contributors take the reader to diverse sites, including brothels, blues clubs, dance clubs, elite schools, detention centers, advocacy organizations, and public sidewalks in Canada, Italy, Spain, United Arab Emirates, Mozambique, South Africa, and the United States. Geographies of Privilege is the perfect teaching tool for courses on social problems, race, class and gender in Geography, Sociology and Anthropology.
Keywords: afrique; afrique du sud; amériques; anthropologie; approches et analyses; canada; classe sociale; discipline; environnement; espagne; europe; géographie; italie; mozambique; outils; ouvrages de références; privilèges; racisme; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; émirats arabes unis; états-unis

Patriarcat (Théorie du) - Delphy, Christine (Dictionnaire critique du féminisme, 2004)
Keywords: approches et analyses; cours; discipline; europe; fem1000; france; féminisme matérialiste; outils; ouvrages de références; patriarcat; premier cycle; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions

Différence des sexes (Théorie de la) - Collin, Françoise (Dictionnaire critique du féminisme, 2000)
Dictionnaire théorique et politique, pluriel et engagé, il pose comme centrale la problématique de la domination entre les sexes et ses conséquences. Critique à double titre, il expose les controverses théoriques et politiques qui traversent la pensée et le mouvement féministe, et se propose de déconstruire certains concepts classiques des sciences sociales.
Keywords: 1900-1999; approches et analyses; cours; différence des sexes; europe; fem1000; france; histoire et politique; militance; outils; ouvrages de références; premier cycle; périodes historiques; régions géographiques; sexisme; systèmes d'oppressions; thématiques